Single institute experience of intraoperative radiation therapy in early-stage breast cancer. Issue 46 (19th November 2021) - Chi, Mau-Shin; Ko, Hui-Ling; Chen, Chang-Cheng; Hsu, Chung-Hsien; Chen, Liang-Kuang; Cheng, Fiona Tsui-Fen
Abstract : Abstract: Intraoperative radiation therapy (IORT) is an alternative to whole breast irradiation in selected early-stage breast cancer patients. In this single institute analysis, we report the preliminary results of IORT given by Axxent Electronic Brachytherapy (eBT) system. Patients treated with lumpectomy and eBT within a minimum follow-up period of 12 months were analyzed. Eligible criteria include being over the age of 45, having unifocal invasive ductal carcinoma (IDC) or ductal carcinoma in situ <3 cm in diameter, not exhibiting lymph node involvement on preoperative images, and negative sentinel lymph node biopsy. The eBT was given by preloaded radiation plans to deliver a single fraction of 20 Gray (Gy) right after lumpectomy. From January 2016 to April 2019, a total of 103 patients were collected. There were 78 patients with IDC and 25 with ductal carcinoma in situ. At a mean follow-up time of 31.1 months (range, 14.5–54.0 months), the local control rate was 98.1%. Two IDC patients had tumor recurrences (1 local and 1 regional failure). Post-IORT radiotherapy was given to 4 patients. There were no cancer related deaths, no distant metastases, and treatment side effects greater than grade 3 documented. We report the largest single institute analysis using the eBT system in Taiwan. The low recurrence and complication rates at a 31.1 month follow-up time support the use of the eBT system in selected early-stage breast cancer patients.